As figuras de linguagem no processo de constituição do texto em o sermão do monte - Nunes, Maria de Lourdes Lima (2011)
Many studies have been undertaken in order to develop theories in the field of text analysis. For the diversity of study methods and the great variety of meanings that may result from such studies, it is necessary to apply these procedures to assess its effectiveness in practice. This work is studied, based on theories of discourse analysis and text linguistics, the effect of a sense of figurative language in the translated text in three versions that aim to reach different audiences. The text chosen is The Sermon on the Mount, in the Bible, the passage of the Gospel of Matthew, chapters 5-7. The examination of the text include the identification of the terms of the figurative meaning and its relation to other elements of phrasal construction, followed by application of the theories of the discursive possibilities for finding meaning and purpose as a form of rhetoric.